DOES DIGITAL FINANCIAL INCLUSION MATTER FOR BANK RISK-TAKING? EVIDENCE FROM THE DUAL-BANKING SYSTEM - Hasanul Banna; Md Rabiul Alam (Bank Indonesia, 2021)
This paper examines the nexus between digital financial inclusion (DFI) and levels of bank risk-taking, using a sample of 283 commercial banks (Islamic and conventional) from six countries over the period 2011 to 2019 and deploying panel-corrected standard errors, two-stage least squares-instrumental variables and dynamic panel two-step generalized method of moments estimators. The findings suggest that Islamic banks take more risks than their counterpart conventional banks. The empirical evidence also indicates that an increase in the DFI index score reduces the overall level of bank risktaking and increases that of banking stability for commercial and conventional banks compared to Islamic ones. A strong association between DFI and bank risk-taking suggests that DFI not only reduces the default risk, leverage risk and portfolio risk of banks, but also increases financial mobility in the sample countries. Consequently, an inclusive digitalised banking industry ensures sustainable economic growth, which is likely to help maintain financial sustainability in times of crisis such as the Covid-19 pandemic. Our results are shown to be robust by various robustness checks. The study contributes to both the Islamic and conventional banking, as well as the digital financial inclusion, literature. The findings of the study provide various policy implications for policymakers and standard-setters in the countries examined.